2022
DOI: 10.1097/cad.0000000000001285
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA sterile alpha motif domain containing 4A contributes to cell 5-fluorouracil resistance in colorectal cancer by regulating the miR-545-3p/6-phosphofructo-2-kinase/fructose-2,6-bisphosphataseisotype 3 axis

Abstract: Colorectal cancer (CRC) is one of the most fatal cancers in the world. Circular RNA sterile alpha motif domain containing 4A (circSAMD4A) was found to be highly expressed in CRC and promoted the tumorigenesis of CRC. However, the role of circSAMD4A in 5-fluorouracil (5-Fu) resistance of CRC is yet to be clarified. This study is designed to investigate the function of circSAMD4A in 5-Fu resistance of CRC and its potential molecular mechanism. Quantitative real-time PCR was used to detect the expression levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Bioinformatic prediction and verification of dual luciferase reporter assay and RNA pull-down assay showed miR-545-3p as a potential miRNA target for circADAM9. Published studies have shown that miR-545-3p could be sequestered by some circRNAs to alleviate the malignant development of cancers, such as lung 29 30 31 and colorectal cancers 32 33 . The current study found reduced expression of miR-545-3p in patients with DN, and the protective effects of circADAM9 suppression in HG-induced HMCs were reversed upon miR-545-3p silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic prediction and verification of dual luciferase reporter assay and RNA pull-down assay showed miR-545-3p as a potential miRNA target for circADAM9. Published studies have shown that miR-545-3p could be sequestered by some circRNAs to alleviate the malignant development of cancers, such as lung 29 30 31 and colorectal cancers 32 33 . The current study found reduced expression of miR-545-3p in patients with DN, and the protective effects of circADAM9 suppression in HG-induced HMCs were reversed upon miR-545-3p silencing.…”
Section: Discussionmentioning
confidence: 99%
“…As another common anti-cancer drug, 5-FU is incorporated into DNA or RNA due to its similarity with the pyrimidines that are fundamental components of these molecules, leading to cell death and inhibiting cancer progression [ 121 ]. Increased expression of circSAMD4A in CRC [ 122 ] and circNRIP1 in GC [ 79 ] contribute to 5-FU resistance by upregulating glycolysis. Therefore, targeting these circRNAs may overcome this type of drug resistance in GI cancers.…”
Section: Clinical Significance Of Glycolysis-associated Circrnas In G...mentioning
confidence: 99%
“…Besides, 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase isotype 3 (PFKFB3) is a pivotal enzyme for glucose metabolism. Gao Y and the colleagues have found circSAMD4A could facilitate the expression of PFKFB3 and promote glycolysis by sponging miR-545-3p ( 83 ). Moreover, PKM2 is another crucial enzyme for glycolysis in cancer.…”
Section: Regulation Of Glucose Metabolic Reprogramming By Circrnasmentioning
confidence: 99%
“…Some dysregulated circRNAs participate in regulating chemoresistance and glycolysis in CRC, such as circSAMD4A ( 83 ) and ciRS-122 ( 81 ). CircSAMD4A contributes to 5-Fu resistance via targeting miR-545-3p/PFKFB3 and regulating glycolysis of CRC cells, while knockdown of circSAMD4A improves the sensitivity of 5-Fu ( 83 ).…”
Section: Regulation Of Glucose Metabolic Reprogramming By Circrnasmentioning
confidence: 99%
See 1 more Smart Citation